Salviae miltiorrhizae radix and puerariae lobatae radix herbal formula improves circulation, vascularization and gait function in a peripheral arterial disease rat model. (10th January 2021) - Koon, Chi-Man; Wing-Shing Cheung, David; Wong, Pui-Han; Wat, Elaine; Ng, Sau-Kuen; Cheung, Wing-Hoi; Fu-Yuen Lam, Francis; Chook, Ping; Fung, Kwok-Pui; Leung, Ping-Chung; Yan, Bryan P.
Abstract: Ethnopharmacological relevance: DG is a herbal formula, containing the root of Salvia miltiorrhiza Bunge (Danshen) and the root of Pueraria lobate (Willd.) Ohwi (Gegen), has a history of usage in China for cardiovascular protection and anti-atherosclerosis. Aim of the study: The present study aims to determine the beneficial effect of DG on the hind-limb ischemia rat model which mimics peripheral arterial disease (PAD) and its vasodilative effect on isolated femoral artery. Materials and methods: The vasodilatory effects were assessed by contractile responses to DG in the isolated femoral artery and its underlying mechanisms were evaluated by the involvement of endothelium, potassium channel and calcium channel. For hind-limb ischemia study, treatment outcomes were assessed by evaluating hind-limb blood flow, functional limb recovery, muscle histology and angiogenesis. Results: Our results demonstrated positive dose-dependent vasodilatory response to DG via an endothelium-independent mechanism that involved inwardly rectifying K + channels and Ca 2+ channels. We also demonstrated significant improvement in blood perfusion and micro-vessel density in the ischemic limb and positive effects in functional limb recovery. Conclusion: In conclusion, our study supported the potential use of DG as a novel treatment for symptomatic PAD. Graphical abstract: Image 1 Highlights: DG improved limb function in a hind-limb ischemia rat model. DG improved hind-limb blood perfusion through vasodilation and angiogenesis. Vasodilatory effects of DG were endothelium-independent by inhibition of Ca 2+  influx and opening of inwardly rectifying K +  channel (KIR ).